1994
DOI: 10.3109/02688699409029622
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of intracerebral haematoma as shown on CT scanning after aneurysmal subarachnoid haemorrhage

Abstract: In a prospective study of 1076 consecutive patients with aneurysmal subarachnoid haemorrhage (SAH), CT was carried out in 815 patients. CT visible intracerebral haematoma (ICH) was found in 42.6% of the 815 patients. There were no differences in age, pre-existing hypertension or sex between patients with or without ICH. Patients with ICH were in poorer clinical condition on admission, and had a poorer mental outcome and a higher mortality at the 2-year follow-up examination compared with patients without ICH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
38
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 12 publications
9
38
0
Order By: Relevance
“…The clinical outcome of SAH patients with ICH is usually worse than that of SAH patients without ICH [12, 20]. Heuer et al [21] showed that the ICP increases in over half of all patients with SAH, particularly among those with a poor grade who also have ICH.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcome of SAH patients with ICH is usually worse than that of SAH patients without ICH [12, 20]. Heuer et al [21] showed that the ICP increases in over half of all patients with SAH, particularly among those with a poor grade who also have ICH.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it remains a difficulty in neurosurgery. Aneurysmal SAH coexisted with brain hernia is often accompanied by intracerebral hematoma; when such a condition occurs, patient's condition will turn more serious and higher disability and fatality rates will occur, compared with aneurysmal SAH without intracerebral hematoma (5). Therefore, early diagnosis and accordingly-decided rational treatment greatly influence the prognosis of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, the average outcome is worse than in patients with purely subarachnoid blood (26). When a large haematoma is the most likely cause of the poor condition on admission, the immediate evacuation of the haematoma should be seriously considered (with simultaneous clipping of the aneurysm if it can be identified), often with the aneurysm having been demonstrated only by MR angiography or CT angiography.…”
Section: Intracerebral Haematomamentioning
confidence: 99%